Laser-driven proton acceleration via excitation of surface plasmon polaritons into TiO2 nanotube array targets. (2nd October 2020) - Cristoforetti, G; Baffigi, F; Brandi, F; D'Arrigo, G; Fazzi, A; Fulgentini, L; Giove, D; Koester, P; Labate, L; Maero, G; Palla, D; Romé, M; et al.
Abstract: In this paper we report the measurement of laser-driven proton acceleration obtained by irradiating nanotube array targets with ultrashort laser pulses at an intensity in excess of 10 20 W cm −2 . The energetic spectra of forward accelerated protons show a larger flux and a higher proton cutoff energy if compared to flat foils of comparable thickness. Particle-In-Cell 2D simulations reveal that packed nanotube targets favour a better laser-plasma coupling and produce an efficient generation of fast electrons moving through the target. Due to their sub-wavelength size, the propagation of e.m. field into the tubes is made possible by the excitation of Surface Plasmon Polaritons, travelling down to the end of the target and assuring a continuous electron acceleration. The higher amount and energy of these electrons result in turn in a stronger electric sheath field on the rear surface of the target and in a more efficient acceleration of the protons via the target normal sheath acceleration mechanism.